Overcoming evanescent field decay using 3D-tapered nanocavities for on-chip targeted molecular analysis - Kumar, Shailabh; Park, Haeri; Cho, Hyunjun; Siddique, Radwanul H.; Narasimhan, Vinayak; Yang, Daejong; Choo, Hyuck (Nature communications, 2020)
Enhancement of optical emission on plasmonic nanostructures is intrinsically limited by the distance between the emitter and nanostructure surface, owing to a tightly-confined and exponentially-decaying electromagnetic field. This fundamental limitation prevents efficient application of plasmonic fluorescence enhancement for diversely-sized molecular assemblies. We demonstrate a three-dimensionally-tapered gap plasmon nanocavity that overcomes this fundamental limitation through near-homogeneous yet powerful volumetric confinement of electromagnetic field inside an open-access nanotip. The 3D-tapered device provides fluorescence enhancement factors close to 2200 uniformly for various molecular assemblies ranging from few angstroms to 20 nanometers in size. Furthermore, our nanostructure allows detection of low concentration (10 pM) biomarkers as well as specific capture of single antibody molecules at the nanocavity tip for high resolution molecular binding analysis. Overcoming molecule position-derived large variations in plasmonic enhancement can propel widespread application of this technique for sensitive detection and analysis of complex molecular assemblies at or near single molecule resolution. Plasmon-enhanced fluorescence is strictly dependent on molecule size and surface position, restricting application of diversely sized molecules. Here, the authors overcome this by introducing a 3D tapered gap plasmon nanocavity with fluidic access and near homogeneous confinement of the electromagnetic fields.